2021
DOI: 10.52633/jemi.v3i1.51
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Person-Job Fit, Person-Organization Fit on Job Satisfaction

Abstract: It has been observed in many organizations that some employees feel unsatisfied with their work, the justification behind the dissatisfaction could be due to various reasons such as skills and abilities of an employee if not match with the job or task requirements or the work assigned is not according to individual capabilities. As far as the previous studies are concerned, it is revealed that person job fit, and person organization fit have a significant positive relationship with job satisfaction. Thus, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Likewise, number of other OB theorists have talked in favor of the above stated interrelationship. Similarly, Research conducted by (Hussain et al, 2017;Shah & Ayub, 2021) have found a positive relationship between person job and organization fit, with that of employees firms commitment. Similarly, (Jin et al, 2018;Tao, 2018) have talked in favor of increased affective commitment of employees in presence of their fit with both the firm, and the job they perform.…”
Section: Person Job Fit/person-organization Fit and Affective Commitmentmentioning
confidence: 81%
“…Likewise, number of other OB theorists have talked in favor of the above stated interrelationship. Similarly, Research conducted by (Hussain et al, 2017;Shah & Ayub, 2021) have found a positive relationship between person job and organization fit, with that of employees firms commitment. Similarly, (Jin et al, 2018;Tao, 2018) have talked in favor of increased affective commitment of employees in presence of their fit with both the firm, and the job they perform.…”
Section: Person Job Fit/person-organization Fit and Affective Commitmentmentioning
confidence: 81%
“…According to (Shah & Ayub, 2021) the worker shows his disappointment with the dissatisfaction he feels through four ways such as leaving the job and looking for another job; doing the job with the meanings of being late or not coming to work to make a mistake intentionally; expressing his dissatisfied feelings to the boss aiming for the situation to be resolved; and the latter waiting with confidence that the organization and management can do the best thing.…”
Section: Theory Of Job Satisfactionmentioning
confidence: 99%
“…According to Kurniawan, (2021) job satisfaction depends on person job fit, where all company employees have their own uniqueness and what is sought is the match with the conditions of the work carried out in order to increase satisfaction and obtain optimal results based on their abilities and expertise. Shah & Ayub, (2021) say that there is an attachment between person-job fit and job satisfaction which shows a significant positive effect. Companies engaged in contracting are also one of the specific focuses for assigning employees according to their abilities, where good employee performance will affect the company.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, relevant sectors with IT, such as telecom, can be worthy industries in Bangladesh for further investigation. In the Pakistani pharmaceutical setting, Shah and Ayub (2021) and Tran (2023) found that person-organization fit has a positive and significant impact on job satisfaction, and that organization fit and employee engagement can also be investigated. Therefore, it becomes obvious that there is a knowledge gap in the investigation of organizational fit and employee engagement.…”
Section: Introductionmentioning
confidence: 99%